The values of late-modern landscape architecture in view of Mihály Mőcsényi's public park design - Bakay, Eszter; Szilágyi, Kinga (4D Journal of Landscape Architecture and Garden Art, 2019)
Mihály Mőcsényi’s active work in landscape architecture and garden design marks the so-called late-modern period embracing some three decades starting from his service as a garden trainee in Switzerland in 1947-48. His vice-presidency and presidency years at IFLA left him little leisure, but in the 90’s he undertook some design work again at home and in Vienna, too. However, in terms of landscape architecture this period already represented the postmodern, or more precisely the end of it, the era of seeking new perspectives. The aim of our study was to find out to what extent the characteristic functional and space composition principles of the period(s) were reflected in the plans of professor Mőcsényi. What are the typical “Mőcsényi-like” composition principles, space structural elements and hallmarks independent of age and trend, that can be interpreted as the heritage of Hungarian late-modern landscape architecture? Are there any, and if yes, what are those “eternal” design principles that should be preserved as values in terms of landscape architectural object-design?
Keywords: Late-modern; Public park; Mőcsényi